2007
DOI: 10.1159/000111576
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Prevalence Rates of Multiple Sclerosis: A Critical Review

Abstract: Review of the recent medical literature raises doubts about the reliability of reported prevalence rates of multiple sclerosis (MS). Many published prevalence rates are inflated. Some studies have shown that relying on clinical information and MRI interpretation leads to one third of incorrect MS diagnoses. The most important error is failing to distinguish between the clinical and MRI characteristics of MS and of disseminated encephalomyelitis (DEM) in both their acute and relapsing forms. The diagnostic crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 67 publications
(36 reference statements)
0
40
0
7
Order By: Relevance
“…On the other hand, if one takes into account that the in the present study we surveyed all major hospitals and all MRI services in the city, as well as the file of the State Health Agency, which provides free medication for all relapsing-remitting MS patients in the state, and additionally scrutinized the files of the MS societies in the city, one may be able to evaluate how careful we have been to catch all MS patients living in the city. The resulting data provide, for the first time in Latin America, the onset-adjusted prevalence rate, which is a more precise measure than crude prevalence 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, if one takes into account that the in the present study we surveyed all major hospitals and all MRI services in the city, as well as the file of the State Health Agency, which provides free medication for all relapsing-remitting MS patients in the state, and additionally scrutinized the files of the MS societies in the city, one may be able to evaluate how careful we have been to catch all MS patients living in the city. The resulting data provide, for the first time in Latin America, the onset-adjusted prevalence rate, which is a more precise measure than crude prevalence 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, however, many of these epidemiological studies lack consistent methodological features, such as strict diagnostic criteria, well defined study populations or geographical areas, and complete case ascertainment 3 . Such faults have rendered their results unreliable for comparisons with established data from other geographical areas 2,3 . In Latin America, surveys on the epidemiology of MS are still scanty and most of them exhibit these methodological limitations [4][5][6][7][8] .…”
mentioning
confidence: 99%
“…Given the differences in prevalence rates among populations, it is likely that MS is influenced by an interaction between genetic and environmental factors 1 . In the last 20 years, a large number of studies on MS prevalence have been published, mostly in Europe and North America, revealing rates ranging from 60 to 200 per 100,000 inhabitants 2 .…”
mentioning
confidence: 99%
“…Palais des Congrés de Montréal, Montreal, Quebec, Canada, June [1][2][3][4]2011 The submission deadline for abstracts is January 10, 2011. Information on online abstract submission and the meeting can be found on the CMSC Annual Meeting website at http://annualmeeting.mscare.org.…”
Section: Resultsmentioning
confidence: 99%
“…2 Respiratory impairment in neurologic or neuromuscular injuries or disorders such as MS includes 1) difficulty in ventilation due to inspiratory muscle weakness; 2) difficulty in coughing due to weakness of the expiratory muscles, upper-airway (glottic) muscle, and inspiratory muscles; and 3) risk of aspiration of fluids due to upper-airway muscle weakness. 3 Actual prevalence rates of respiratory problems in individuals with MS are not known 4 ; however, due to the prevalence of MS in the United States (approximately 400,000) and worldwide (2.5 million), a significant number of individuals may be at risk. 5 Very few studies address differences in respiratory impairment relative to type of MS, although Grasso et al 6 reported greater respiratory abnormalities in patients with cerebellar involvement.…”
mentioning
confidence: 99%